Effect of Salt and Fresh Water Concentration on Polyisoprenoid Content in Bruguiera cylindrica Seedlings - Basyuni, Mohammad; Nainggolan, Santi Sari; Qurrahman, Taufiq; Hasibuan, Poppy Anjelisa Zaitun; Sumaiyah, Sumaiyah; Sumardi, Sumardi; Siregar, Etti Sartina; Nuryawan, Arif (Open Access Macedonian Journal of Medical Sciences, 2019)
BACKGROUND: Mangrove forest is a typical forest found along the coast or river mouth which is affected by tides and salinity. Although polyisoprenoid was widespread in the plant kingdom, the physiological roles of these compounds are not well understood, especially from mangrove plants. It is therefore essential to characterize the polyisoprenoid content under abiotic stress. AIM: This study aimed to determine the effect of salinity and subsequent fresh water change on polyisoprenoids concentration in Bruguiera cylindrica seedlings. METHODS: Bruguiera cylindrica planted in a greenhouse for three months under various salinity concentrations. After three months grew under variable salinity, these seedlings were then divided into two treatment groups, and grown for another three months: one continuously in a salt solution and another in fresh water to relieve salt stress. The leaves and roots of B. cylindrica seedlings were harvested after six months of cultivation. The leaves and roots of B. cylindrica seedlings were extracted for polyisoprenoids content and composition analyzed using two-dimensional thin layer chromatography. RESULTS: Polyisoprenoids composition under salinity and subsequent fresh water with dominating dolichols (more than 90%) were found in leaves and roots of B. cylindrica seedlings referring type I of polyisoprenoid composition. The carbon chain length of dolichols located in the leaves and roots were ranging from C75–C100 and C75–C105, respectively. CONCLUSION: Dolichol dominated over polyprenol both in B. cylindrical leaves and roots under salinity and subsequent relief supported the previous finding on the predominance dolichols over polyprenols in mangrove plants. The present study suggested the significance of dolichols in the adaptation to cope with salt stress and or water stress.